The Hundred Years' War on Palestine: A History of Settler Colonialism and Resistance, 1917-2017 - Khalidi, Rashid (New York : Picador, Metropolitan Books, Henry Holt and Company, 2021)
A landmark history of one hundred years of war waged against the Palestinians from the foremost US historian of the Middle East, told through pivotal events and family history. In 1899, Yusuf Diya al-Khalidi, mayor of Jerusalem, alarmed by the Zionist call to create a Jewish national home in Palestine, wrote a letter aimed at Theodore Herzl: the country had an indigenous people who would not easily accept their own displacement. He warned of the perils ahead, ending his note, 'in the name of God, let Palestine be left alone.' Thus Rashid Khalidi, al-Khalidi's great-great-nephew, begins this sweeping history, the first general account of the conflict told from an explicitly Palestinian perspective. Drawing on a wealth of untapped archival materials and the reports of generations of family members--mayors, judges, scholars, diplomats, and journalists--The Hundred Years' War on Palestine upends accepted interpretations of the conflict, which tend, at best, to describe a tragic clash between two peoples with claims to the same territory. Instead, Khalidi traces a hundred years of colonial war on the Palestinians, waged first by the Zionist movement and then Israel, but backed by Britain and the United States, the great powers of the age. He highlights the key episodes in this colonial campaign, from the 1917 Balfour Declaration to the destruction of Palestine in 1948, from Israel's 1982 invasion of Lebanon to the endless and futile peace process. Original, authoritative, and important, The Hundred Years' War on Palestine is not a chronicle of victimization, nor does it whitewash the mistakes of Palestinian leaders or deny the emergence of national movements on both sides. In reevaluating the forces arrayed against the Palestinians, it offers an illuminating new view of a conflict that continues to this day. --.
The first declaration of war, 1917-1939 -- The second declaration of war, 1947-1948 -- The third declaration of war, 1967 -- The fourth declaration of war, 1982 -- The fifth declaration of war, 1987-1995 -- The sixth declaration of war, 2000-2014 -- Conclusion: A century of war on Palestinians.
new book 2024 winter.
Includes bibliographical references (pages 257-302) and index.
Keywords: Palestinian Arabs -- Politics and government -- 20th century; Palestinian Arabs -- Politics and government -- 21st century; Settler colonialism -- Palestine -- History -- 20th century; Settler colonialism -- Palestine -- History -- 21st century; Arab-Israeli conflict; Palestine -- History -- 20th century; Palestine -- History -- 21st century; Palestine -- Politics and government -- 1917-1948; Palestine -- Politics and government -- 1948-; Israel -- Politics and government -- 20th century; Israel -- Politics and government -- 21st century; Israel -- History -- 20th century; Israel -- History -- 21st century